Low carb - high carb diet plan to increase special endurance of elite climbers - Galysheva, S.; Legchinova, S. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop and evaluate the effectiveness of the low carbohydrate -high carbohydrate diet plan for climbers to be used in the precompetitive period.Methods and structure of the study. Sampled for the study were 12 elite climbers (CMS and MS of Russia; Russian, European and World champions). The Harvard step test was used to determine the level of development of the subjects` overall endurance (cardiovascular system functionality). A specific test method was used to evaluate the local muscle en-durance in the forearm: standard-grip hang with both hands with 70% of maximum weight for 8 seconds with 5-sec rest intervals. The total execution time was recorded.The level of development of strength (special) endurance was assessed by the number of grips and finger holds made. The athletes were to climb a moderate-difficulty route as long as possible without rest. The number of grips and finger holds was calculated. This test was performed on an artificial climbing wall.After initial testing, the climbers were offered a low carb-high carb diet plan.Results and conclusion. The authors have developed and adapted a 7-day low carb-high carb diet plan for elite climb-ers. The tests conducted upon its introduction into the climber training process proved to be effective in increasing special and local endurance in the precompetitive period. This diet plan can be recommended to increase the glycogen levels in the climbers in the precompetitive period.